2016
DOI: 10.20471/acc.2016.55.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Physical Activity in Pregnancy Using Questionnaires: A Meta-Analysis

Abstract: SUMMARY -Physical activity (PA) during normal pregnancy has various positive eff ects on pregnant women's health. Determination of the relationship between PA and health outcomes requires accurate measurement of PA in pregnant women. Th e purpose of this review is to provide a summary of valid and reliable PA questionnaires for pregnant women. During 2013, Pubmed, OvidSP and Web of Science databases were searched for trials on measurement properties of PA questionnaires for pregnant population. Six studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Using validated questionnaires to measure physical activity is simple and inexpensive, yet these tools have limitations due reliability and construct validity. 3 , 4 Furthermore, other studies suggest that there is only fair agreement in self-reported physical activity using questionnaires and objectively measured physical activity (e.g., pedometers, accelerometers) and that self-reported activity is typically higher than what accelerometers record. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Using validated questionnaires to measure physical activity is simple and inexpensive, yet these tools have limitations due reliability and construct validity. 3 , 4 Furthermore, other studies suggest that there is only fair agreement in self-reported physical activity using questionnaires and objectively measured physical activity (e.g., pedometers, accelerometers) and that self-reported activity is typically higher than what accelerometers record. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…71 PPAQ is a semiquantitative and subjective instrument, which has been validated 70 and is considered one of the most valid and reliable questionnaires for the assessment of PA level in pregnant women. 72 Our research group has translated PPAQ to Danish and validated it in a Danish pregnant population. 73 The doubly labelled water technique is the 'gold standard' technique to measure free-living energy expenditure objectively and is safe, even for pregnant women, as it relies on stable, non-radioactive isotopes.…”
Section: Additional Outcomes Complementary Measures Of Physical Activitymentioning
confidence: 99%
“…In this sense, in the questionnaire, the non-active criterion corresponds to a weekly expenditure of up to 225 METs, and being physically active corresponds to an expenditure above this threshold, which is consistent with the results of previous studies that have applied this instrument in a pregnant population. [24][25][26][27] Therefore, the cut-off point for active and non-active women was established to be 225 METs per week.…”
Section: Data Sourcesmentioning
confidence: 99%